Effect of Coix Seed on the Rheological and Structural Properties of Wheat Dough and Noodle Quality - WU Yingmei, XU Longquan, YU Yunliu, LUO Guangjie, WANG Chengli, PU Dingfang, HUANG Qun (Shipin Kexue)
The effect of coix seed flour (0%–25%) on the rheological and structural properties of wheat dough and noodle quality was investigated. The addition of coix seed flour was found to enhance the elasticity of dough, which may be attributed to the fact that small starch particles increase the filling capacity within the dough matrix. This increase subsequently resulted in more complete and uniform structure of dough. Moreover, setback viscosity rose to 1 095 cP. The rapid water absorption of coix seed starch led to changes in the secondary structure of proteins in dough. The proportion of β-sheet markedly increased, whereas the proportion of α-helix decreased with increasing level of coix seed flour substitution. Meanwhile, coix seed flour substitution significantly reduced the estimated glycemic index of noodles. Correlation analysis revealed that pasting parameters had significant effects on the evaluation of noodle quality. This study provides a foundation for researchers to substitute wheat flour with coix seed flour.